Metrological analysis of laser active control devices of details dimensions using corundum tips - E. V. Leun; V. I. Leun; A. E. Shahanov (Омский научный вестник)
The article is devoted to calculation of measurement error of contact of active control devices (ACD) of product dimensions using artificially created corundum tips. It is shown that most of it is determined by the temperature error that occurs due to its thermal expansion of the tip when heated as a result of mechanical contact with the detail. The calculations are based on the formation in the tip of the route of the input and reflected optical flows at an angle to its front surface providing a complete internal reflection in the contact area with the detail. The calculation of measurement error is made when creating a reference channel in the laser interferometer, fixing the displacement of the back side of the tip from its thermal expansion. A significant reduction of measurement error for this case is shown.